Translating research into homes and schools: strategies for parents, educators and researchers - Doehring, Peter (Henry Stewart Talks, 2010)
Evidence-based practice (EBP), Reducing problem behavior, Opportunities and barriers for research and families, Strategies for researchers, Focus on meaningful and measureable progress, Research-school partnerships, Becoming familiar with the best research review, Developing a data-based culture and infrastructure, School-family partnerships, Future directions: system-wide research, EBP standards